2001
DOI: 10.1177/109467050133004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Price Perceptions in an Integrated Model of Behavioral Intentions

Abstract: Compared to the emphasis that service quality research has received in service marketing, much less work has been done on the role of price perceptions and their effect on customer retention. This article seeks to fill this gap in the literature. The authors build propositions of price’s role vis-à-vis customer value, satisfaction, and behavioral intentions and then test these propositions using empirical data from the banking industry in the United States and New Zealand. Their findings indicate that (a) pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
266
1
24

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(314 citation statements)
references
References 52 publications
23
266
1
24
Order By: Relevance
“…Greater perceived value leads to increased levels of satisfaction (Anderson, 1995). Some studies have also identified perceived value as an antecedent to customer satisfaction (Bolton & Drew, 1991;Fornell et al, 1996;Sajeev & Colgate, 2001). Customers are more satisfied when their interaction with a business provides value, which leads to a higher customer retention rate (Barnes, 2001).…”
Section: Customer Perceived Value and Satisfactionmentioning
confidence: 99%
“…Greater perceived value leads to increased levels of satisfaction (Anderson, 1995). Some studies have also identified perceived value as an antecedent to customer satisfaction (Bolton & Drew, 1991;Fornell et al, 1996;Sajeev & Colgate, 2001). Customers are more satisfied when their interaction with a business provides value, which leads to a higher customer retention rate (Barnes, 2001).…”
Section: Customer Perceived Value and Satisfactionmentioning
confidence: 99%
“…The perceived value measure is often operationalized as customers' responses to a "worth what paid for" question (Gale 1994;Keiningham et al 2007;Varki and Colgate 2001). In the current study, perceived value was measured with five items concerning price/value for money adapted from Sweeney and Soutar (2001).…”
mentioning
confidence: 99%
“…A utilização dessas estratégias deve-se ao fato de o preço ser uma variável relevante na decisão de compra (HEIL;HELSEN, 2001;VARKI;COLGATE, 2001; O efeito do formato de... TONI;MAZZON, 2011;SOOD;KELLER, 2012). Assim, a determinação do preço final de venda do produto e seu formato de apresentação são fundamentais para estimular a Intenção de Compra e a Percepção de Qualidade (CHEN; MONROE; LOU, 1998;GREWAL et al, 1998).…”
Section: Introductionunclassified